Ratio Legis and Effectiveness of Tax Transaction Recording System Implementation to Increase Regional Revenue - Ari Samudro Pribadi (Unifikasi: Jurnal Ilmu Hukum, 2025)
This study aims to examine ratio legis and the effectiveness of tax transaction recording system, as well as the contribution to improving taxpayer compliance and regional revenue. The research method used is socio-legal research with a research approach, namely empirical law and non-legal with a conceptual approach, legislation, and empirical data sourced from interviews. The results showed that ratio legis for implementing tax transaction recording system to increase regional revenue was based on several regulations, including the Law on Financial Relations between the Central and Regional Governments, the Government Regulation on General Provisions for Regional Taxes and Levies, as well as the Regional Regulation on Regional Taxes and Levies. These regional regulations serve as the legal basis for the collection of taxes and levies in Nganjuk Regency. In terms of effectiveness, tax transaction recording system promotes transparency, enabling business owners to better understand tax obligations. Consequently, good tax education can prepare a more competent workforce and contribute to regional revenue. An effective tax recording system is crucial in supporting the achievement of Sustainable Development Goal number 8, namely Decent Work and Economic Growth. In conclusion, tax transaction recording system, such as Tapping Box, has the potential to improve taxpayer compliance and regional revenue. However, dissatisfaction among taxpayers remains a challenge. This study suggests intensification of socialization about the benefits and procedures for using Tapping Box, ensuring that taxpayers understand and appreciate individual role in taxation system.